Tears of pearl - Alexander, Tasha (New York Minotaur Books, 2009)
Honeymooning in Constantinople, newlyweds Emily and Colin Hargreaves find a young harem girl murdered and promise a heartbroken father they'll find his daughter's killer, a promise that soon leads Emily into the forbidden world of the Sultan's harem where she quickly discovers that its mysterious, sheltered walls offer no protection from a ruthless murderer.
115265
Keywords: Hargreaves, Emily, -- Lady (Fictitious character) -- Fiction; 1288-1918; British -- Turkey -- Fiction; Murder -- Fiction; British; Turkey -- History -- Ottoman Empire, 1288-1918 -- Fiction; Historical fiction; Detective and mystery fiction; Fiction; History; Mystery fiction